Laringotraqueoscopia flexível na decanulação de pacientes com traqueostomia : Otimização de segurança ao paciente - Lemos, Mauricio Medeiros (2016)
Assess the use of laryngo-tracheoscopy in the decannulation of patients with tracheostomy. We have studied 100 patients, aged between 18 and 80, tracheostomized, who indicated decannulation. They undertook the cannula occlusion for three minutes so that phonation and ventilation were evaluated, followed by the examination. We compared the indication of decannulation by clinical criteria with the diagnosis of laryngo-tracheal wounds recognized after the ending of the flexible laryngo-tracheostopy. The Myer-Cotton criteria were used as a reference to classify the laryngotracheal disease. In the 89 patients who had clinical criteria, laryngo-tracheoscopy identified minor injuries - Cotton I, out of 54 of the ones who were able to be dacannulated with out patient follow-up, 8 showed injuries - Cotton II being decannulation not recommended. 11 patients had no speech and do not tolerate occlusion cannula not being decannulated. The flexible laryngo-tracheoscopy identified places and extension of laryngotracheal disease in patients who met the clinical criteria for the removal of tracheal cannula. This exam was safe and useful as a routine in the evaluation of patients who met the decannulation criteria.